Miss Morgan's book brigade : a novel - Charles, Janet Skeslien (Atria Books, 2024)
"1918: As the Great War rages, Jessie Carson takes a leave of absence from the New York Public Library to work for the American Committee for Devastated France. Founded by millionaire Anne Morgan, this group of international women help rebuild devastated French communities just miles from the front. Upon arrival, Jessie strives to establish something that the French have never seen-children's libraries. She turns ambulances into bookmobiles and trains the first French female librarians. Then she disappears. 1987: When NYPL librarian and aspiring writer Wendy Peterson stumbles across a passing reference to Jessie Carson in the archives, she becomes consumed with learning her fate. In her obsessive research, she discovers that she and the elusive librarian have more in common than their work at New York's famed library, but she has no idea that their paths will converge in surprising ways across time. Based on the extraordinary little-known history of the women who received the Croix de Guerre medal for courage under fire, Miss Morgan's Book Brigade is a tribute to the resilience of the human spirit, the power of literature, and ultimately the courage it takes to make a change"--